REMODELING OF THE GASTRIC FUNDIC VASCULATURE UNDER THE EFFECT OF COMPLEX OF MONOSODIUM GLUTAMATE, SODIUM NITRITE AND PONCEAU 4R - Yachmin А.І.; Yeroshenko, G.A.; Shevchenko, K.V.; Bilash, S.M.; Lysachenko, O.D.; Sokolenko, V.M.; Sharlai, N.M.; Klepets, O.V. (World of Medicine and Biology, 2021)
The paper presents the data of morphometric study of the effect of the food additives complex on the state of the vasculature of the stomach fundus under the action of the complex of monosodium glutamate, sodium nitrite and Ponceau 4R food additives. It was found that in the early stages of the experiment there was spasm of blood vessels of the hemomicrocirculatory bed due to the direct effect of food additives on the mucous membrane, which led to increased diameters of submucosal vessels as a result of hemodynamic conditions of the mucous membrane. Further development of the inflammatory reaction and the phenomenon of hypoxia led to compensatory-restorative reactions, but complete recovery did not occur, which at the end of the experiment was expressed by decompensation of the resistive link, metabolic spasm and increased lumen of the capacitive link.